Ant species (Hymenoptera: Formicidae) in the three forests of the Ischigualasto Provincial Park, a protected area of the Monte Desert, Argentina - EMILCE AMATTA; LUIS A. CALCATERRA; STELLA . M GIANNONI (Society for Indonesian Biodiversity, 2018)
Amatta E, Calcaterra LA, Giannoni SM. 2018. Ant species (Hymenoptera: Formicidae) in the three forests of the Ischigualasto Provincial Park, a protected area of the Monte Desert, Argentina. Biodiversitas 19: 831-839. Deforestation and over-grazing mediated by the humans have caused a serious process of desertification in the Argentine Monte Desert, which threats biodiversity of this ecosystem. Forests provide important resources and refuge for animal species, such as ants. The objective of this work was to survey the ant fauna of dryland forests of Ischigualasto Provincial Park, a protected area located in the hyper-arid Monte Desert ecoregion in the province of San Juan, Argentina. Ant species were surveyed in summer in three types of forests (Prosopis, Ramorinoa and Bulnesia forests), using a combination of sampling methods: pitfall-traps, baiting, and hand collection. A total of 33 ant species were collected, of which 17 are new records for the Monte Desert and Dry Chaco and 24 for the San Juan province. The species richness is within the range reported for other Argentine desert and semi-desert areas. Prosopis forest was the richest with 32 species (24 exclusive), followed by Ramorinoa and Bulnesia forests with 11 and 4 species, respectively. This study contributes to improve the knowledge of ant fauna in desert habitats of the world, especially those inhabiting Prosopis forests, which are the most important ant diversity hotspots within the hyper-arid desert.